A Feasibility Study of AquaWash: Wash2Go Laundry Shop and H2Go Water Refilling Station - Arcilla, Allyza Marie B., Berceles, Janina N., Dionisio, Alliah Mae A., Guia, Christine Mae Grace C., Justiniano, Justine Nicole P., Toleros, Sofia Mariel C., Velasco, Jenilyn T. 4 0 16; 5
Abstract: This study explores the establishment of AquaWash, a dual- service business combining Was2Go, a laundry service, and H2G0, a water refilling station It aims to provide convenient and cost-efficient solutions to meet the growing demand for accessible water and laundry services in urban and suburban areas. The study evaluates key aspects, including market feasibility. technical feasibility. requirements, financial feasibility, and potential challenges. Results indicate strong market demand for both services, supported by strategic location and competitive pricing. AquaWash demonstrates significant potential to address the needs of time-conscious customers while offering a sustainable business model. Keywords: AquaWash, Wash2Go, H2Go, Water Refilling, Laundry. Sustainability
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2